SEM-EDX Pigment Analysis and Multi-Analytical Study of the Ground and Paint layers of Francesco Fedrigazzi's painting from Kostanje - Jelena Zagora (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Francesco Fedrigazzi, Venetian by birth, was a painter active in Istria and Dalmatia in the late 17th and the early part of the 18th century. In the second decade of the 18th century he painted an altar painting for the church of Saint Michael in Kostanje. This painting was later removed from the church and stored in the attic of the parish house. Unfavourable conditions in which it was stored resulted in extensive damage. As part of her Master's thesis, the author investigated stratigraphy and composition of the painting's ground and paint layers using a number of techniques. UV fluorescence analysis and digital X-ray imaging were conducted at the Conservation-Restoration Department of the Arts Academy of the University in Split. Scanning electron microscopy – energy dispersive X-ray analysis (SEM-EDX) was done by a research centre for materials in Istria, METRIS. The investigation gave insight into Fedrigazzi's painting technique and revealed the pigments that he used in his colours.